2022
DOI: 10.3389/fphar.2022.1046269
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid suppresses apoptosis of high-grade serous ovarian cancer cells by inducing autophagy activity and promotes cell-cycle progression via EGFR-PI3K/Aurora-AThr288-geminin dual signaling pathways

Abstract: Lysophosphatidic acid (LPA) and geminin are overexpressed in ovarian cancer, and increasing evidence supports their contribution to ovarian tumor development. Here, we reveal that geminin depletion induces autophagy suppression and enhances reactive oxygen species (ROS) production and apoptosis of high-grade serous ovarian cancer (HGSOC) cells. Bioinformatics analysis and pharmacological inhibition studies confirm that LPA activates geminin expression in the early S phase in HGSOC cells via the LPAR1/3/MMPs/EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…LPA is also critically involved in the regulation of cell cycles and proliferation. LPA, via LPAR1 and 3, activates the epidermal growth factor receptor (EGFR)/PI3K/mammalian target of rapamycin (mTOR) and Aurora kinase pathways to promote geminin expression and stabilisation, which subsequently regulate DNA replication, cell cycle progression and proliferation of ovarian cancer cells [107]. A similar mechanism of LPA/geminincontrolled cell cycle progression has also been described in gastric cancer cells [108].…”
Section: Lpa In Proliferationmentioning
confidence: 87%
“…LPA is also critically involved in the regulation of cell cycles and proliferation. LPA, via LPAR1 and 3, activates the epidermal growth factor receptor (EGFR)/PI3K/mammalian target of rapamycin (mTOR) and Aurora kinase pathways to promote geminin expression and stabilisation, which subsequently regulate DNA replication, cell cycle progression and proliferation of ovarian cancer cells [107]. A similar mechanism of LPA/geminincontrolled cell cycle progression has also been described in gastric cancer cells [108].…”
Section: Lpa In Proliferationmentioning
confidence: 87%
“…The absence of NDUFA10, a vital subunit of mitochondrial complex I, leads to functional deficiency of the complex, which results in mitochondrial impairment [56]. Previous studies have also found an association between NDUFA10 and several diseases, such as nonalcoholic steatohepatitis [57], type 2 diabetes [58], Alzheimer's disease [59] and Leigh disease [38]. According to a previous study, decreased levels of NDUFA10 protein impair mitochondrial function, increase mitochondrial ROS production, and ultimately lead to disruption of cardiac structure and function [60].…”
Section: Discussionmentioning
confidence: 99%